Experimental investigation on the fracture behaviour of black shale by acoustic emission monitoring and CT image analysis during uniaxial compression. Issue 1 (15th January 2018) - Wang, Y; Li, C H; Hu, Y Z
Summary: Plenty of mechanical experiments have been done to investigate the deformation and failure characteristics of shale; however, the anisotropic failure mechanism has not been well studied. Here, laboratory Uniaxial Compressive Strength tests on cylindrical shale samples obtained by drilling at different inclinations to bedding plane were performed. The failure behaviours of the shale samples were studied by real-time acoustic emission (AE) monitoring and post-test X-ray computer tomography (CT) analysis. The experimental results suggest that the pronounced bedding planes of shale have a great influence on the mechanical properties and AE patterns. The AE counts and AE cumulative energy release curves clearly demonstrate different morphology, and the 'U'-shaped curve relationship between the AE counts, AE cumulative energy release and bedding inclination was first documented. The post-test CT image analysis shows the crack patterns via 2-D image reconstructions, an index of stimulated fracture density is defined to represent the anisotropic failure mode of shale. What is more, the most striking finding is that the AE monitoring results are in good agreement with the CT analysis. The structural difference in the shale sample is the controlling factor resulting in the anisotropy of AE patterns. The pronounced bedding structure in the shale formation results in an anisotropy of elasticity, strength and AE information from which the changes in strength dominate the entire failure pattern of the shale samples.